2004
DOI: 10.1364/opex.12.001575
|View full text |Cite
|
Sign up to set email alerts
|

Angular and polarization properties of a photonic crystal slab mirror

Abstract: It was recently demonstrated that a photonic crystal slab can function as a mirror for externally incident light along a normal direction with near-complete reflectivity over a broad wavelength range. We analyze the angular and polarization properties of such photonic crystal slab mirror, and show such reflectivity occurs over a sizable angular range for both polarizations. We also show that such mirror can be designed to reflect one polarization completely, while allowing 100% transmission for the other polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 8 publications
6
103
0
Order By: Relevance
“…It has been shown that polarization selectivities of 100% and 0% for orthogonal polarizations can be obtained by using rectangular holes in place of circular holes [64]. This dependence can be simulated using FDTD methods, as shown in Figure 10B, with the use of elliptical holes rather than rectangular.…”
Section: Integrated Mirrors Based On Photonic-crystal Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that polarization selectivities of 100% and 0% for orthogonal polarizations can be obtained by using rectangular holes in place of circular holes [64]. This dependence can be simulated using FDTD methods, as shown in Figure 10B, with the use of elliptical holes rather than rectangular.…”
Section: Integrated Mirrors Based On Photonic-crystal Membranesmentioning
confidence: 99%
“…Figures 9B and 9C show the electric field profile of light trapped within the PC slabs and the refractive index profile, respectively. Guided fere with the out-of-plane external light allowing for complete constructive or destructive interference on opposite sides of the slab [63,64].…”
Section: Integrated Mirrors Based On Photonic-crystal Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as literature survey on optical mirror is concerned, a lot of similar type of research works deal with the same [9 -12]. In reference [9] authors discuss the construction of optical mirror using photonic crystal slab. Similarly, in reference [10], photonic crystal mirror is investigated using III-V/Si integrated devices.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Fano resonances, out-of-the-plane optical mode coupling in 2D PCS becomes feasible because the in-plane guided resonances above the lightline are strongly coupled to the out-of-the-plane radiation modes due to phase matching provided by the periodic lattice structure. 5 In recent years, devices based on Fano resonances such as narrowband filters 1,4 and broadband reflectors [6][7][8] have been reported. Recently, we also reported narrowband Fano filters and broadband membrane reflectors with patterned silicon nanomembranes ͑SiNM͒ transferred onto glass and flexible polyethylene terephthalate substrates, 9 employing a low temperature wet-transfer process.…”
mentioning
confidence: 99%